Highlights from Faraday discussion 170: Challenges and opportunities of modern mechanochemistry, Montreal, Canada, 2014. Issue 29 (18th March 2015) - Friščić, Tomislav; James, Stuart L.; Boldyreva, Elena V.; Bolm, Carsten; Jones, William; Mack, James; Steed, Jonathan W.; Suslick, Kenneth S.
Abstract : This Faraday Discussion brought together a diversity of academic and industrial researchers, experimentalists and theoreticians, students, and researchers, to discuss the changing face of mechanochemistry. Abstract : The Faraday Discussion Mechanochemistry: From Functional Solids to Single Molecules which took place 21–23 May 2014 in Montreal, Canada, brought together a diversity of academic and industrial researchers, experimentalists and theoreticians, students, as well as experienced researchers, to discuss the changing face of mechanochemistry, an area with a long history and deep connections to manufacturing, that is currently undergoing vigorous renaissance and rapid expansion in a number of areas, including supramolecular chemistry, smart polymers, metal–organic frameworks, pharmaceutical materials, catalytic organic synthesis, as well as mineral and biomass processing and nanoparticle synthesis.